Preparation of a novel cellulose-based immobilized heteropoly acid system and its application on the biodiesel production - Zhang, Dong-Yang; Duan, Ming-Hui; Yao, Xiao-Hui; Fu, Yu-Jie; Zu, Yuan-Gang (Fuel (Guildford), 2016)
[Display omitted] •Cellulose beads were prepared using environmental friendly ILs.•HPWs were first immobilized on the cellulose beads with high immobilized amount.•The cellulose-based immobilized heteropoly acid can be successfully used on the biodiesel production.•The cellulose-based immobilized heteropoly acid can be reused more than 7 times. Porous cellulose beads (CBs) were prepared using ionic liquid as solvent and then further modified using different reagents which were ethylenediamine (EDA), diethylenetriamine (DETA), triethylene tetramine (TETA) and 4-aminostyrene (AST). These CBs were used as carrier for immobilization of H3PW12O40 (HPW). The immobilized catalysts were characterized by FT-IR, scanning electron microscopy, XRD, ICP atomic emission spectrophotometer. The results indicated that CB-(AST-HPW)n possessed higher amounts of HPW and stronger catalytic activity for biodiesel production. After using CB-(AST-HPW)n for yellow horn oil esterification, the conversion yield reached 96.22% under optimal conditions. The final product of biodiesel prepared with CB-(AST-HPW)n was of high quality. We conclude that cellulose-based immobilized HPW is a novel catalyst potentially suited for biodiesel production.